2009
DOI: 10.1523/jneurosci.5698-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Nitric Oxide Is a Key Promoting Factor for Initiation of Seizure-Like Events in Hippocampal and Entorhinal Cortex Slices

Abstract: Nitric oxide (NO) modulates synaptic transmission, and its level is elevated during epileptic activity in animal models of epilepsy. However, the role of NO for development and maintenance of epileptic activity is controversial. We studied this aspect in rat organotypic hippocampal slice cultures and acute hippocampal-entorhinal cortex slices from wild-type and neuronal NO synthase (nNOS) knock-out mice combining electrophysiological and fluorescence imaging techniques. Slice cultures contained nNOS-positive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 80 publications
3
67
0
Order By: Relevance
“…In line with this observation, it has been reported that in the hippocampus and entorhinal cortex NO is involved in the induction, but not the maintenance of seizure-like activity. 45 NO is a diffusible neuronal messenger that activates sGC and increases intracellular cGMP levels during an ischemic episode in the brain. 46 Accordingly, we found that inhibition of sGC by ODQ, and of PKG by Rp-8Br-PET-cGMP prevented i-LTP induction.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this observation, it has been reported that in the hippocampus and entorhinal cortex NO is involved in the induction, but not the maintenance of seizure-like activity. 45 NO is a diffusible neuronal messenger that activates sGC and increases intracellular cGMP levels during an ischemic episode in the brain. 46 Accordingly, we found that inhibition of sGC by ODQ, and of PKG by Rp-8Br-PET-cGMP prevented i-LTP induction.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used NOS activity inhibitors to understand the involvement of the NOS isoforms in the mechanism of OGD-induced cell damage and in the neuroprotective effect of GUO. The non-selective NOS inhibitor L-NAME (1 mM), the selective iNOS inhibitor 1400 W (50 μM), and the selective nNOS inhibitor 7-NI (100 μM) were used [10,35]. GUO prevented cell viability decrease in hippocampal slices subjected to OGD, similarly to L-NAME (Fig.…”
Section: Evaluation Of Putative Antioxidant Properties Of Guanosinementioning
confidence: 99%
“…However, the hyperactivation of NMDA receptors in postsynaptic neurons produces excessive nNOS activity and subsequently inflammatory reactions inducing iNOS expression at glial cells, allowing massive and uncontrolled NO release that may be damaging for the neighboring neurons [8]. Furthermore, the negative effects of excessive NO generation are caused by the endogenous formation of the peroxynitrite anion (ONOO − ) rather than NO itself [10]. ONOO − is formed by the spontaneous reaction of NO with superoxide anion (O 2 − ) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have demonstrated that nitric oxide produced by nNOS initiates seizure-like events in the hippocampus and entorhinal cortex [128]. Furthermore, an increase in superoxide synthesis follows immediately in response to the seizure.…”
Section: Seizures Electromagnetic Fields and Sulfate Synthesis By Rbcsmentioning
confidence: 99%